Multatuli in Zombieland - Vermoortel, Philip (Werkwinkel, 2017)
In 1860, the Dutch author Multatuli (pen name of Eduard Douwes Dekker) published Max Havelaar, which was to become the most famous nineteenth-century Dutch novel. In 2016, the book was rewritten by Martijn Adelmund as a book in which also zombies play a role. By doing so, Adelmund follows a fifteen-year-old American literary tradition to rewrite literary masterpieces as zombie books. Since Max Havelaar neither contains many characters nor descriptions of Indonesian nature and has a rather simple plot, Adelmund decided to mix the book with another nineteenth-century Dutch literary masterpiece: Louis Couperus’ De stille kracht. The purpose is to make secondary school pupils read the original Max Havelaar again and encourage them to compare the two versions in order to develop a critical understanding of Dutch colonial history and its present-day consequences. The review focuses on the way Adelmund combined the two classic books, reshaped the plot and added parts of his own. Attention is paid to the way in which the original language was modernized and to the question whether this book really can or will help young students to read the original. However noble Adelmund’s objectives may be, it is very improbable that he will manage to realize them since the quality of the novel he created leaves a lot to be desired.